Development and applications of ATM selected readings - Toy, Mehmet (Institute of Electrical and Electronics Engineers, Inc., 1996)
Contains over 50 of the leading articles published on the subject of asynchronous transfer mode, covering such topics as the fundamentals of ATM, switching techniques, traffic analysis, network management, and specific applications.